Parto vaginal después de una cesárea previa, Hospital San Juan de Dios, Cali (Colombia): Estudio de cohorte A cohort study of vaginal birth following prior cesarean section in the San Juan de Dios hospital, Cali, Colombia - Olga Lucía Cuero-Vidal; Carlos Andrés Clavijo-Prado (Federación Colombiana de Obstetricia y Ginecología, 2011)
Objetivo: determinar la incidencia de parto vaginal después de una cesárea previa y evaluar la capacidad predictiva del puntaje predictor de parto vaginal descrito por Flamm en 1997. Materiales y métodos: estudio de cohorte retrospectivo de mujeres con antecedente de cesárea y embarazo de al menos 37 semanas, que consultaron al Hospital San Juan de Dios de Cali (HSJD) entre mayo 30 de 2007 y mayo 30 de 2008. Se calculó la tasa de parto vaginal y se evaluó la sensibilidad, especificidad, valores predictivos positivo (VPP) y negativo (VPN) y las razones de verosimilitud positiva (RVP) y negativa (RVN) del puntaje predictor de parto vaginal después de una cesárea cuando los valores de estos son de 4 o más y de 8 o más. Resultados: la proporción de parto vaginal en este grupo fue del 20,3%. El 36% de las gestantes con puntajes entre 4 y 7 tuvieron parto vaginal y el 83% de las gestantes con 8 o más puntos. Con un punto de corte ≥ 4 puntos la sensibilidad fue de 85,7%, la especificidad 69,1%, VPP 41,3% y VPN 95%, RVP 2,8 y RVN 0,2. Si el punto de corte fue ≥ 8 la sensibilidad fue de 83,3%, la especificidad 82,6%, VPP 17,9% y VPN 99,1%, RVP 4,8 y RVN 0,2. Conclusión: la frecuencia de parto vaginal posterior a cesárea es del 20%. Las gestantes con puntajes menores de 4 tuvieron una baja probabilidad de tener un parto vaginal. Objective: determining the incidence of vaginal birth following a prior cesarean section and evaluating the predictive ability of the vaginal birth predictor score on the admission scoring system described by Flamm in 1997. Materials and methods: this was a retrospective cohort study of women having undergone a prior cesarean section and then a pregnancy lasting at least 37 weeks who had consulted at the San Juan de Dios hospital in Cali (HSJD) between May 30th 2007 and May30th 2008. The vaginal birth rate was calculated and sensitivity, specificity, positive (PPV) and negative predictive values (NPV) were evaluated, as were positive (RVP) and negative verisimilitude ratios (RVN) regarding vaginal birth predictor score following a cesarean when their scores were 4 or more and 8 or more. Results: there were 20.3% vaginal births in this group; 36% of the pregnant women having scores between 4 and 7 had undergone vaginal birth and 83% of the expectant mothers scoring 8 or more. A ≥4 points cut-off point gave 85.7% sensitivity, 69.1% specificity, 41.3% Positive Predictive Value (PPV) and 95% Negative Predictive Value (NPV) and 2.8 Positive likelihood ratio P LR(+) and 0.2 Negative likelihood ratio (NLR). If cut-off point were ≥8, then this gave 83.3% sensitivity, 82.6% specificity, 17.9% PPV, 99.1% NPV, 4.8 RVP and 0.2 RVN. Conclusion: vaginal birth frequency following a cesarean section was 20%. Pregnant women having scores less than 4 had a low probability of having a vaginal birth.